Sleep disturbance and psychotic-like experiences among urban adolescents with and without parental migration - Wang, Dongfang; Ma, Zijuan; Zhai, Shuyi; Sun, Meng; Fan, Fang (Frontiers in Public Health, 2023)
Aim Sleep disturbance was closely associated with an increased risk of psychotic-like experiences (PLEs). This study aims to explore the association between sleep disturbance and PLEs among urban adolescents with and without parental migration. Methods A total of 67, 532 urban Chinese adolescents were recruited in a large web-based survey during April 21st to May 12th, 2021. In our study, sleep disturbance, PLEs, family function, school climate, and a series of socio-demographic were assessed. And hierarchical logistic regression analyses were performed to examine influential factors associated with PLEs. Results Urban left-behind children (LBC) had a higher prevalence of sleep disturbance and PLEs than non-LBC. After controlling for confounders, parental migration was associated to PLEs with weak significance (OR = 1.19). Meanwhile, sleep disturbance was found to be a robust risk factor for PLEs (OR = 3.84 and 4.09), with or without the effect of parental migration. In addition, better family function and school climate has significant association with decreased risk of PLEs. Conclusion Adolescents with sleep disturbance are more likely to report PLEs. Adolescents' PLEs preventive strategies could focus on reducing sleep disturbance related symptoms as well as improving family function and school climate.